2017
DOI: 10.1097/gox.0000000000001563
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Complications in Expander-Based Breast Reconstruction: Multivariate Analysis in Asian Patients

Abstract: Background:There have been many studies examining risk factors for complications in expander-based breast reconstruction after mastectomy, and some patient factors have been identified as risk factors. However, most of the previous studies were based on Caucasian patients.Methods:Asian patients who had a tissue expander placed for immediate breast reconstruction between January 2006 and December 2015 (363 patients and 371 expanders) were analyzed retrospectively. Univariate and multivariate analyses were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…Yalanis et al reported their results on 253 breast reconstructions, in which mastectomy weights of greater than 500 g were associated with a 10 times higher rate of skin necrosis and 18 times higher when the mass of resected tissue was greater than 1000 g. 10 A second study showed that mastectomy specimens greater than 500 gm are significantly associated with all categories of complications, including seroma formation and skin necrosis. 11,12 Consistent with this finding, the affected patient had very high fluid accumulation volumes (Fig. 1).…”
Section: Discussionsupporting
confidence: 80%
“…Yalanis et al reported their results on 253 breast reconstructions, in which mastectomy weights of greater than 500 g were associated with a 10 times higher rate of skin necrosis and 18 times higher when the mass of resected tissue was greater than 1000 g. 10 A second study showed that mastectomy specimens greater than 500 gm are significantly associated with all categories of complications, including seroma formation and skin necrosis. 11,12 Consistent with this finding, the affected patient had very high fluid accumulation volumes (Fig. 1).…”
Section: Discussionsupporting
confidence: 80%
“…Smoking was found to increase the risk of developing postoperative complications after reconstruction with autologous flaps (11)(12)(13)(14) and following alloplastic BR (15)(16)(17). However, not all research is equivocal on this aspect (18)(19)(20). For example, a study on tissue expansion did not find smoking to be a risk factor for developing complications, possibly due to low smoking incidence in that study population (8%) (21).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the disparity in results published on smoking and BMI in relation to complications after alloplastic BR (18)(19)(20)(21)26), we set out to evaluate the effect of smoking, BMI ⩾ 25, and other possible risk factors on the occurrence of complications after alloplastic BR at our study centers. The outcome of this study may help improve individual counseling for women who contemplate to undergo BR with implants or tissue expanders (TEs) after prophylactic mastectomy or breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…(470.17 ± 243.15 versus 319 ± 173.8, respectively), meaning larger skin flap surface area, which can cause less blood flow to the distal skin edges [26][27][28].…”
Section: Discussionmentioning
confidence: 99%